Defecating disorders: a common cause of constipation in women. (July 2015) - Dimitriou, Nikoletta; Shah, Vikas; Stark, Diane; Mathew, Ronnie; Miller, Andrew S; Yeung, Justin MC
Defecating disorders are a common and complex problem. There are a range of anatomical and functional bowel abnormalities that can lead to this condition. Treatment is difficult and needs a multidisciplinary approach. First line treatment for defecating disorders is conservative. For those that fail conservative treatment, some may respond to surgical therapy but with variable results. The aim of this review is to offer an overview of defecating disorders as well as provide an algorithm on how to diagnose and treat them with the help of a multidisciplinary and multimodal approach.